Transverse and longitudinal beam dynamics studies at the Fermilab photoinjector - J.-P. Carneiro; N. Barov; H. Edwards; M. Fitch; W. Hartung; K. Floettmann; S. Schreiber; M. Ferrario (Physical Review Special Topics. Accelerators and Beams, 2005)
The Fermilab photoinjector produces electron bunches of 1–12 nC charge with an energy of 16–18 MeV. Detailed measurements and optimization of the transverse emittance have been carried out for a number of beam line optics conditions, and at a number of beam line locations. The length of the bunches has also been measured, first for an uncompressed beam (as a function of the charge) and then for a compressed beam of 8 nC charge (as a function of the 9-cell cavity phase). These measurements are presented and compared with the simulation codes HOMDYN and ASTRA.